From Cath Lab to Surgery Room: Multimodal Imaging of a Giant Left Main Aneurysm. (September 2018) - Cammertoni, Federico; Bruno, Piergiorgio; Chiariello, Giovanni Alfonso; Merlino, Biagio; Mazza, Andrea; Pavone, Natalia; Nesta, Marialisa; Iafrancesco, Mauro; Colizzi, Christian; Massetti, Massimo
Abstract : Supplemental Digital Content is available in the text.